Technical advances for measurement of gas exchange at the whole plant level: Design solutions and prototype tests to carry out shoot and rootzone analyses in plants of different sizes. (January 2023) - Patono, Davide L.; Eloi Alcatrāo, Leandro; Dicembrini, Emilio; Ivaldi, Giorgio; Ricauda Aimonino, Davide; Lovisolo, Claudio
Abstract: To measure gas exchange at the whole plant (WP) level, design solutions were provided and prototypes of gas-exchange systems (GESs) were tested to carry out shoot and rootzone analyses in plants of different sizes. A WP-GES for small herbaceous plants was tested on the ability to maximize the net assimilation rate of CO2 in lettuce plants grown either under blue-red light or upon full spectrum artificial light. A WP-GES for large woody plants was tested during an experiment describing the drought stress inhibition of grapevine transpiration and photosynthesis. Technical advances pointed to optimize: i) the choice of cuvette material and its technical configuration to allow hermetic isolation of the interface shoot-rootzone, to avoid contamination between the two compartments, and to allow climate control of both shoot and rootzone cuvettes, ii) accurate measurements of the mass air-flow entering both cuvettes, and iii) an adequate homogenization of the cuvette air volume for stable and accurate detection of CO2 and H2 O concentration in cuvettes before and after CO2 and H2 O contamination of the air volumes exerted by plant organs. Highlights: Technical advances for measurement of gas exchange in whole plants are proposed. Design solutions to carry out analyses in plants of different sizes are shown. Prototypes are proposed and tested in root and shoot of lettuces and grapevines.